Oral berotralstat for the prophylaxis of hereditary angioedema attacks in patients in Japan: A phase 3 randomized trial. Issue 6 (23rd December 2020) - Ohsawa, Isao; Honda, Daisuke; Suzuki, Yusuke; Fukuda, Tomoo; Kohga, Keisuke; Morita, Eishin; Moriwaki, Shinichi; Ishikawa, Osamu; Sasaki, Yoshihiro; Tago, Masaki; Chittick, Greg; Cornpropst, Melanie; et al.
Abstract: Background: With no approved treatments in Japan for the prevention of hereditary angioedema (HAE) attacks, there is a significant unmet need for long‐term prophylactic therapies for Japanese patients with HAE. Berotralstat (BCX7353) is an oral, once‐daily, highly selective inhibitor of plasma kallikrein in development for prophylaxis of angioedema attacks in HAE patients. Methods: APeX‐J is a phase 3, randomized, double‐blind, placebo‐controlled, parallel‐group, 3‐part trial conducted in Japan (University Hospital Medical Information Network identifier, UMIN000034869; ClinicalTrials.gov identifier, NCT03873116). Patients with a clinical diagnosis of type 1 or 2 HAE underwent a prospective run‐in period of 56 days to determine eligibility, allowing enrollment of those with ≥2 expert‐confirmed angioedema attacks. Patients were randomly assigned (1:1:1) and stratified by baseline attack rate (≥2 vs. <2 expert‐confirmed attacks/month between screening and randomization) to receive once‐daily berotralstat 110 mg, berotralstat 150 mg, or placebo. The primary endpoint was the rate of expert‐confirmed angioedema attacks during dosing in the 24‐week treatment period. Results: Nineteen patients were randomized to receive once‐daily berotralstat 110 mg ( n = 6), berotralstat 150 mg ( n = 7), or placebo ( n = 6). Treatment with berotralstat 150 mg significantly reduced HAE attacks relative to placebo (1.11 vs. 2.18 attacks/month, p = .003). The most frequently reported treatment‐emergent adverse events (TEAEs) in berotralstat‐treated patients ( n = 13) were nasopharyngitis ( n = 4, 31%), abdominal pain, cough, diarrhea, and pyrexia ( n = 2 each, 15%). Conclusions: Orally administered, once‐daily berotralstat 150 mg significantly reduced the frequency of HAE attacks and was safe and well tolerated, supporting its use as a prophylactic therapy in patients with type 1 or 2 HAE in Japan. Abstract : APeX‐J is a phase 3, placebo‐controlled trial conducted in Japan to assess the efficacy and safety of oral berotralstat in patients with HAE. Patients were randomized 1:1:1 to receive once‐daily berotralstat 110 mg, berotralstat 150 mg, or placebo. Berotralstat 150 mg significantly reduced the frequency of HAE attacks compared with placebo, supporting its use as a prophylactic therapy. Abbreviation: HAE, hereditary angioedema.